The Impact of Ease of Access and Service Level Agreements (SLAs) on Multipurpose Financing Growth at PT. Bank Sumut Sharia Business Unit - Anang Andrian; Muhammad Irwan Padli Nasution; Andri Soemitra (CV. Radja Publika, 2026)
The development of the Islamic banking industry in Indonesia has shown a positive trend in recent years. However, competition with conventional banking requires Islamic banks to continuously improve service quality to attract and retain customers. One product with high growth potential is multipurpose financing. This study aims to analyze the effect of ease of access and Service Level Agreements (SLAs) on the growth of multipurpose financing in Islamic banking. The research method used is a quantitative approach. The independent variables consist of ease of access and SLA, while the dependent variable is the growth of multipurpose financing. The results show that ease of access and SLA have a positive effect on the growth of multipurpose financing. The easier access to services and the faster the financing process provided by PT. Bank Sumut Sharia Business Unit, the growth of multipurpose financing will show an upward trend. This study implies that PT. Bank Sumut Sharia Business Unit needs to strengthen digital transformation and increase service speed to enhance the competitiveness of financing products.